2019
DOI: 10.3390/w11101992
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Types of Permeable Pavements for Urban Runoff Mitigation in the Semi-Arid South Texas, U.S.A

Abstract: This study examines the hydrologic and environmental performance of three types of permeable pavement designs: Porous Concrete Pavement (PCP), Permeable Interlocking Concrete (PICP), and Interlocking Block Pavement with Gravel (IBPG) in the semi-arid South Texas. Outflow rate, storage, Normalized Volume Reduction (NVR), Normalized Load Reductions (NLR) of Total Suspended Solids (TSS), and Biochemical Oxygen Demand (BOD5) were compared to results obtained from adjacent traditional pavements at different regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…A study examining hydrologic alterations of stormwater by three types of permeable pavements showed that peak flows were lowered between 31% and 100% across all three types of pavements. PC pavements were best at eliminating surface runoff compared to interlocking block pavement with gravel, and PICP (Alam, Mahmoud, Jones, Bezares‐Cruz, & Guerrero, 2019a). The porosity of PC pavements ranging from 20% to 30% was shown to have no effect on the fatigue life of pavement sections subjected to repeated wheel loads (AlShareedah, Nassiri, & Dolan, 2019).…”
Section: Permeable Pavementmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining hydrologic alterations of stormwater by three types of permeable pavements showed that peak flows were lowered between 31% and 100% across all three types of pavements. PC pavements were best at eliminating surface runoff compared to interlocking block pavement with gravel, and PICP (Alam, Mahmoud, Jones, Bezares‐Cruz, & Guerrero, 2019a). The porosity of PC pavements ranging from 20% to 30% was shown to have no effect on the fatigue life of pavement sections subjected to repeated wheel loads (AlShareedah, Nassiri, & Dolan, 2019).…”
Section: Permeable Pavementmentioning
confidence: 99%
“…The reduction of TSS was greatest (80%) by PC compared with other pavements tested. Other pavements tested comprised PICB, and interlocking block pavements with gravel (Alam et al, 2019a). BOD5 removal with interlocking block pavements with gravel was greatest (46%) when compared with other pavements.…”
Section: Water Qualitymentioning
confidence: 99%
“…Within the algorithm, the total volume of runoff was calculated by multiplying the rainfall duration by the peak discharge as per flow-volume relationship [55]. The following Equations (4)- (7) were written for the DSS algorithm to calculate 50-and 10-year peak discharge and runoff volume:…”
Section: Dss Algorithm Developmentmentioning
confidence: 99%
“…Urban land developments increased by four times between the years 1945 and 2010 [5], which eventually altered the watershed hydrology and triggered an uncontrolled runoff towards major rivers in the US [6]. The first flush of urban runoff carries non-point source (NPS) pollutant load, which eventually adversely affects the water quality of the watershed [7][8][9]. Since the 1980s, federal and state agencies have been working to update the watershed protection plans and adjust existing drainage policy measures to address the impairment of the US rivers, with the involvement of cities and the Stormwater Task Force (STF) partners [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation